1991
DOI: 10.1161/01.hyp.18.3_suppl.i87
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure levels in black populations in sub-Sahara Africa, the West Indies, and the United States: a meta-analysis.

Abstract: Average systolic blood pressure levels from epidemiological studies conducted on black populations in sub-Sahara Africa were pooled and compared with pooled systolic blood pressure levels from black populations in the northern portion of the Western hemisphere (the West Indies and the United States). Studies published in English that listed systolic blood pressure means and standard deviations and sample sizes in 40-49-year-old men and women were included. Overall, systolic blood pressure levels were higher (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…There is some evidence that people of African origin who were transported as slaves from Africa to the Caribbean, the USA, Western Europe and the UK have even higher blood pressures than residents of cities in West Africa [4]. The factors explaining this second epidemiological transition may be similar to those related to the first transition described earlier.…”
Section: African-origin Populationsmentioning
confidence: 75%
See 1 more Smart Citation
“…There is some evidence that people of African origin who were transported as slaves from Africa to the Caribbean, the USA, Western Europe and the UK have even higher blood pressures than residents of cities in West Africa [4]. The factors explaining this second epidemiological transition may be similar to those related to the first transition described earlier.…”
Section: African-origin Populationsmentioning
confidence: 75%
“…In 'primitive' or unaculturated tribal societies in rural Africa, Asia and South America, hypertension and its complications are rare [1][2][3][4]. By contrast, in urban societies in all parts of the world, hypertension is common.…”
Section: African-origin Populationsmentioning
confidence: 99%
“…2 However, with the exception of South Africa, low rates of hypertension are generally observed among blacks living in Africa. 3 One explanation for the association of skin color and blood pressure (BP) is an imbalance in the distribution of factors that affect BP. Epidemiological studies have identified a number of variables associated with BP levels, including age, gender, body mass index (BMI), sodium intake, potassium intake, socioeconomic status, alcohol consumption, and physical activity.…”
mentioning
confidence: 99%
“…The reverse appears to be true of African Americans [44], which is con sistent with the phenomenon of rural dwelling as a risk factor for PD in the USA. Neverthe less, systolic blood pressure in urban African Americans was still higher than that of urban Parkinson's Disease in Populations of African Origin dwellers in West Africa [44]. We have noted that heart disease and diabetes have a nega tive impact on elderly African American life expectancy [25], If these diseases are them selves risk factors for PD, African Americans would be at double jeopardy from increased risk of PD and high mortality.…”
Section: Risk Factors For Pdmentioning
confidence: 96%
“…These populations are also at an increased risk for stroke [ 11,40] and show an increased preva lence of cardiovascular risk factors such as diabetes [41], abnormalities of coagulation [42] and abnormalities of lipoprotein metabo lism [43], Of particular interest in the present context is a meta-analysis showing that systolic blood pressure levels are higher in African Ameri cans than in people from sub-Saharan Africa [44], Urbanization is associated with in creased systolic blood pressure in sub-Saha ran Africans [45]. The reverse appears to be true of African Americans [44], which is con sistent with the phenomenon of rural dwelling as a risk factor for PD in the USA. Neverthe less, systolic blood pressure in urban African Americans was still higher than that of urban Parkinson's Disease in Populations of African Origin dwellers in West Africa [44].…”
Section: Risk Factors For Pdmentioning
confidence: 99%